Commercial Banks’ Risk-taking Behavior in SAARC Economic Bloc: 2 Stage Least Square Approach - Shumaila Meer Perhiar; Ali Fathoni (Cita Konsultindo Research Center, 2023)
The study examines determinants of the loan loss provision (LLP) of 259 commercial banks of the South Asian Association in the Regional Cooperation (SAARC) from 2010 to 2018. Pool ordinary least square (POLS), fixed effect (FE), panel corrected standard error (PCSE), and two stages least square (2SLS) panel data estimation measures the risk-taking behavior of banks. The results of inflation (INF) as an instrument variable (IV) are highly dependable with a negative impact on loan loss provision (LLP). Credit risk and lending interest rate (LIR) are positively and significantly correlated, an unnecessary quantity of real interest rate (RIR) was not valuable to make profitable returns, particularly throughout the global financial crisis (GFC). LLP is significantly moderated by return on equity (ROE) with a negative interface and facilitated the bank with commercial processes avoiding void bankruptcy. With the allocation of capitalization (CAP), capital adequacy ratio (CAR), and earnings before tax (EBT) to pre-fund credit losses by LLP. Banks increase corporate loans (CORP) for further lending growth and decrease LLP. Liquidity (LIQ) is high so fewer funds allocation is needed for LLP. Endogeneity is measured to check for robustness and showcase the importance of profitability to clarify risk-taking behavior. Government security (GOV) in the local banks does not provide a safety net after the r financial crisis. The profitable business deals, different structure, and inter-operation of losses by investors also cause high LLP, a reason for large impaired loan (IMP). The (SIZE) need to be stabilized with natural logarithm of total assets. Collectively, study relates to the current trickle-down effects due to GFC with policy implications in emerging countries of the economic bloc.